MEDIA PEMBELAJARAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA BERBASIS COMPUTER BASE TRAINING - Wawan Riyanta; Yuwono Wiarco; Handoko Handoko (Jurnal Riset dan Inovasi Pembelajaran, 2022)
Computer Based Training is a teaching material that can support distance lectures that demand more interesting, attractive and efficient media. The making of CBT learning media is carried out using the research and development (R&D) method, making and testing or verifying applications and testing the aplication effectiveness. The development and manufacture of CBT media products uses the Adobe Animate CC platform and then a feasibility test is carried out using a validation questionnaire using a Likert scale that will be carried out by the validator. Trial of learning media Products to 54 respondents and processing the results of the assessment from users obtained very good results with a value of 3.96 and a percentage of 79.3% with details of the assessment of each sub-element of the software engineering aspect of 92%, the learning design aspect by 86% and visual communication aspects by 48%. The visual communication zspect has the lowest assessment result from the other two aspects with 3 (three) visual communication sub aspects that fall into the inappropriate category, namely audio, moving media and interactive layout. The results of this research become an interactive teaching platform for PPI lecturers in 2022.